Hegelian metaphysics - Stern, Robert, 1962- (Oxford : Oxford University Press, 2009)
'Hegel's Metaphysics' is a series of essays analysing the metaphysical ideas and influence of the great German philosopher G. W. F. Hegel (1770-1831). Robert Stern traces the way those ideas were taken up and criticised by the British Idealists and American Pragmatists, and by more contemporary continental philosophers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Metaphysics -- History